R&D Productivity and Firm Size in Semiconductors and Pharmaceuticals: Evidence from Citation Yields - Burak Dindaroğlu (Izmir University of Economics, Department of Economics, 2011)
Using firm level panel data from the U.S., I explore the relationship between firm size and R&D productivity for two important and R&D-intensive industries: Semiconductors and Pharmaceuticals. I employ two measures of a firm's R&D performance: the number of citations received per patented innovation, and the number of citations received per dollar of R&D expenditures. The former is a measure of the average quality of a firm's patents, and the latter is a measure of total R&D output obtained per dollar of investments. I find that the average quality of patents (citations received per patent) falls with firm size in Pharmaceuticals, but there is no relationship between patent quality and firm size in Semiconductors. Citations received per R&D dollar decrease with size in both industries, which is due to the well-documented negative relationship between patents per R&D and firm size.
Keywords: L1; L2; 330; R&D Productivity; Firm size; Patents; Citations; Semiconductors; Pharmaceuticals; Panel data; Betriebsgröße; Industrieforschung; Produktivität; Patent; Panel; Pharmaindustrie; Halbleiterindustrie; USA